Solon of Athens : Poet, Philosopher, Soldier, Statesman. - Owens, Ron. (Liverpool : Liverpool University Press, 2010)
Addresses the historical, social and political contexts within which Solon of Athens instituted wide-ranging reforms to the Athenian constitution (594-93 BCE), the impact of those reforms on the political self-awareness of the archaic Athenians themselves, and the ethical and political philosophies that drove reform.
Description based upon print version of record.
JSTOR
Keywords: Solon, -- approximately 630 B.C.-approximately 560 B.C.; Statesmen -- Greece -- Biography; Poets, Greek -- Biography; Philosophers -- Greece -- Biography; Athens (Greece) -- Politics and government; Hommes d'État -- Grèce -- Biographies; Poètes grecs -- Biographies; Philosophes -- Grèce -- Biographies; HISTORY / Ancient / Greece